DEFENSIVE STRATEGIES OF FAMILY HEALTH TEAMS TO SUFFERING IN THE WORK - Cecília Helena Glanzner; Agnes Olschowsky; Maria de Lourdes Custódio Duarte (Universidade Federal do Paraná, 2018)
Objective: to analyze the defensive strategies that Family Health team professionals use to protect themselves from suffering at work, from the perspective of Work Psychodynamics. Method: This qualitative, descriptive and analytical study was carried out in three Health Units of the South of Brazil, which were intentionally selected, from October to December 2012. All the members of the teams participated in the study, totaling 68 professionals. The information was collected through observation and collective interviews and analyzed according to Bardin, with two categories emerging: collective and individual defense strategies. Results: in the first category, the professionals highlighted the sharing of work issues in meetings and, as individual strategies, denial, rationalization and recognition. Final considerations: theprofessionals sought strategies to cope with the suffering caused by their work using internal and collective resources to confront it and transform the work into a source of pleasure and health.